Effects of cold-plasma on atmospheric pressure on killing of yeast - Thái Văn Phước; Trần Ngọc Đảm (Journal of Technical Education Science, 2013)
The current medical sterilization methods mainly use chemical and temperature. However, these methods have some defects. For examples, using a lot of chemical makes environment polluted and harms people’s health, the time of treating medical instruments lasts long. Besides, only thermal fatigue instruments can be used at high temperature. Therefore, in this paper the cold-plasma model of treating medical tools is designed and manufactured to solve above-mentioned weakness. The advantage of plasma model is that using directly plasma rays to process medical devices, so the time of processing is reduced. Moreover, the environment isn’t polluted. This model uses Argon to make plasma environment. On the other hand, it’s surveyed its ability of eliminating yeasts-Saccharomyces cerevisiae. At last, the result of experiment shows that cold-plasma can kill yeasts absolutely. Plasma’s productivity of processing mostly belongs to processing time as well as its speed (<700 mm/ min). Factors generating plasma such as voltage, electric current, gas flow don’t influence on the productivity of treating a lot. Nevertheless, to ensure a stable and saving energy resource, the model was used at 100V, 2A, 71/min Argon and 400 mm/min of speed..